2010
DOI: 10.2482/haigan.50.841
|View full text |Cite
|
Sign up to set email alerts
|

A Resected Case of Capillary Hemangioma of the Lung Suspected to Be Lung Cancer on Chest Computed Tomography

Abstract: Background.Case. Conclusion.JJLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…2) To our knowledge, only a few cases of SPCH in infants and 7 cases in adults have been reported. [2][3][4][5][6][7] Before Fugo's first SPCH report, Havlik, et al had reported 8 autopsy cases with solitary or paired PCHlike foci that were found incidentally in the lung. These 8 cases did not present with pulmonary hypertension, and PCH was unrelated to the cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…2) To our knowledge, only a few cases of SPCH in infants and 7 cases in adults have been reported. [2][3][4][5][6][7] Before Fugo's first SPCH report, Havlik, et al had reported 8 autopsy cases with solitary or paired PCHlike foci that were found incidentally in the lung. These 8 cases did not present with pulmonary hypertension, and PCH was unrelated to the cause of death.…”
Section: Discussionmentioning
confidence: 99%